2017
DOI: 10.1142/s0218127417300488
|View full text |Cite
|
Sign up to set email alerts
|

Probing Shells Against Buckling: A Nondestructive Technique for Laboratory Testing

Abstract: Abstract. This paper addresses testing of compressed structures, such as shells, that exhibit catastrophic buckling and notorious imperfection sensitivity. The central concept is the probing of a loaded structural specimen by a controlled lateral displacement to gain quantitative insight into its buckling behaviour and to measure the energy barrier against buckling. This can provide design information about a structure's stiffness and robustness against buckling in terms of energy and force landscapes. Develop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Computationally, the only transition which has been followed previously is the simplest unbuckled-singly dimpled pathway, where the dimple is centrally located on the cylinder 32,33 . Meanwhile, local probing of cylindrical shells has been suggested as an experimental technique which may allow the true dimpling transition state to be accessed 26,[34][35][36] . In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computationally, the only transition which has been followed previously is the simplest unbuckled-singly dimpled pathway, where the dimple is centrally located on the cylinder 32,33 . Meanwhile, local probing of cylindrical shells has been suggested as an experimental technique which may allow the true dimpling transition state to be accessed 26,[34][35][36] . In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An explicit link has therefore been made between the ease of single dimple formation and the sensitivity of loaded cylinders to lateral loading 32 . As important for structural applications, it has been suggested that these theoretical minimum-energy barriers can be accessed experimentally via a local probing technique for cylindrical 26,[34][35][36] and spherical shells 37,38 .…”
mentioning
confidence: 99%
“…In the limit for very thin shells, /0 hR → , the energy barriers for prescribed pressure and prescribed volume change are the same. The barrier in the case of prescribed volume change does depend somewhat on / hR , as discussed in [11]. , is given for the two states in a) and the radial displacements of two of the most important modes are presented in b).…”
Section: Selected Results For Buckling Under Uniform Pressure Relevanmentioning
confidence: 99%
“…Recently, a number of publications addressed the energy barrier for axisymmetric dimples on spherical shells by applying an additional point force in order to induce formation of a single dimple, where the point force F is applied, and in order to control the indentation depth ζ by the point force [34,35,40,41]. The barrier state corresponds to an indented state with F = 0 at ζ = ζ B , which is unstable with respect to growth and shrinkage.…”
Section: B Simulation Results For the Energy Barriermentioning
confidence: 99%